(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Scientists in different fields have a high level of cooperation with foreign partners, so they have a high demand for language learning. In modern society, foreign languages are becoming an important component of professional education. People learn such knowledge first at school, college, lyceum, and then at institutes, training courses or independently by getting acquainted with the basic information sets that help to learn a foreign language. In this segment we will explore ways to assess receptive and productive skills.